A case of neonatal single twin flecainide toxicity after therapeutic in utero exposure for fetal SVT. Issue 1 (1st January 2017) - Barot, Sabiha K.; Seslar, Stephen P.; Dolgner, Stephen; Mazor, Suzan S.
ABSTRACT: A 9 hour old twin neonate, who was treated with flecainide in utero for fetal supraventricular tachycardia, presented with hypotension and a wide complex tachycardia concerning for flecainide toxicity. The patient was given a bolus of sodium bicarbonate with transient narrowing of her QRS complex. She was then intubated and started on a sodium bicarbonate drip with full resolution of her wide complex tachycardia within 24 hours. Work up showed no evidence for structural cardiac pathology or infection and she did not experience any further arrhythmias after termination of her presenting wide complex tachycardia. The patient was discharged home at 10 days of age and has had no further sequelae. This case report describes a novel presentation of in utero flecainide toxicity and summarizes the therapies available to treat this rare, but potentially lethal, presentation.